Gastric preparation for magnetically controlled capsule endoscopy: A prospective, randomized single-blinded controlled trial. Issue 1 (January 2018) - Zhu, Shu-Guang; Qian, Yang-Yang; Tang, Xin-Ying; Zhu, Qian-Qian; Zhou, Wei; Du, Han; An, Wei; Su, Xiao-Ju; Zhao, An-Jing; Ching, Hey-Long; McAlindon, Mark Edward; Li, Zhao-Shen; et al.
Abstract: Background and aims: Magnetically controlled capsule endoscopy (MCE) is a novel technique for which there is no agreed gastric preparation. We aimed to determine an optimal standardized gastric preparation regimen. Methods: 120 patients referred for MCE were randomly assigned to gastric preparation with either water alone (A), water with simethicone (B) or water, simethicone and pronase (C). Image quality was assessed using cleanliness and visualization scores, higher scores equating to better image quality. Results: The total cleanliness scores were (mean ± SD) 15.83 ± 2.41 (A), 21.35 ± 1.23 (B), and 20.82 ± 1.90 (C). The total visualization scores (mean ± SD) were 10.75 ± 2.02 (A), 15.20 ± 1.32 (B), and 15.08 ± 1.86 (C). While the image quality of the whole stomach in groups B and C were significantly better than group A (P < 0.0001), there was no statistical difference between group B and C (P > 0.05). MCE detected positive findings in 21 (52.5%), 27 (67.5%) and 21 (53.8%) patients in group A, B and C respectively, with no significant difference between groups (P > 0.5). Conclusions: Simethicone swallowed with water prior to MCE produced the optimal gastric mucosal image quality. The addition of pronase had no demonstrable additional benefit.